Futures Trading and Market Information - Cox, Charles C. (Journal of Political Economy, 1976)
This paper investigates the effect of organized futures trading on information in spot markets. First, a model is developed that relates spot-price behavior and market information. The model can be viewed as a particular efficient markets model; this connection provides additional implications about price behavior and information. Next, price series for six different commodities are investigated for an information effect of futures trading. For each commodity, the empirical evidence indicates that futures trading increases traders' information about forces affecting supply and demand.